2017
DOI: 10.2217/bmm-2017-0072
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Related Association Between Uric Acid, Homocysteine, γ-Glutamyltransferase, Inflammatory Biomarkers and Metabolic Syndrome in Subjects Affected by Obesity

Abstract: UA and γ-glutamyltransferase positively relate to MetS in both genders, although inflammatory abnormalities are closer related to UA and MetS in females. These differences in gender physiology may account for epidemiologic gender disparities and help to develop gender-targeted clinical strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
2
13
1
Order By: Relevance
“…16 UA is a potent antioxidant, although at higher levels may acquire pro-oxidant activity and an adverse role as cardiometabolic risk factor. 13,17 In the present study, UA highest levels were found in subjects with positivity for both tests, and intermediate in those with one test positive, respect to patients with negativity for both tests, possibly reflecting a progressively increased cardiometabolic risk. 18 In our population, concordance between OGTT and HbA1c test to diagnose pre-T2D and T2D was similar in the two genders.…”
Section: Discussionsupporting
confidence: 46%
See 3 more Smart Citations
“…16 UA is a potent antioxidant, although at higher levels may acquire pro-oxidant activity and an adverse role as cardiometabolic risk factor. 13,17 In the present study, UA highest levels were found in subjects with positivity for both tests, and intermediate in those with one test positive, respect to patients with negativity for both tests, possibly reflecting a progressively increased cardiometabolic risk. 18 In our population, concordance between OGTT and HbA1c test to diagnose pre-T2D and T2D was similar in the two genders.…”
Section: Discussionsupporting
confidence: 46%
“…Moreover, increased oxidative stress promotes the autoxidation of glucose to dicarbonyl intermediates in an early step of the Maillard reaction, through which takes place the haemoglobin glycation . UA is a potent antioxidant, although at higher levels may acquire pro‐oxidant activity and an adverse role as cardiometabolic risk factor . In the present study, UA highest levels were found in subjects with positivity for both tests, and intermediate in those with one test positive, respect to patients with negativity for both tests, possibly reflecting a progressively increased cardiometabolic risk …”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…The relationship between aging and GGT that we observed in the Mugello cohort has been previously described in both genders of younger age, whereas males presented higher GGT levels than females [37,38]. Interestingly, GGT is emerging as a new strong and independent MetS determinant in middle age subjects [39,40]. However, our data did not support the association between GGT and MetS, thus GGT could not be an effective marker to identify this condition in nonagenarians.…”
Section: Gamma-glutamyl Transferasecontrasting
confidence: 70%